Análise econômica de tecnologias alternativas apropriadas aos pequenos agricultores - Pinheiro, José César Vieira (1984)
The purpose of this study was to analyse the impact of adopting relevant technologies on farmer's net income and gross profit in several Regional Planning Units (RPUs) in state of Ceará. The relationships between gross income/total cost and gross income/labor days before the adoption of technologies were calculated. The variability in net income and gross profit were calculated through coeficient of variation. Finally, a survey of principal programs and projects which stimulate the utilization of relevant technologies in northeast of Brazil and particularly in Ceará was done. In this study, cross-section data collected by State Agricultural Planning Commission (CEPA-CE) in 1981, was used. Out of the 8 existing technologies, mulch formation, organic manuring and animal cultivation were selected. Parcial budget technique, descriptive and tabular analysis and variance analysis were used. It is concluded that farmers can increase theirs net income and gross profit and reduce risk level by adopting technologies analysed in this study.